Perbandingan Parameter Mutu Crude Palm Oil Produksi PT XYZ Terhadap Ketetapan Mutu Standar Nasional Indonesia - Soliawati Soliawati; Qabul Dinanta Utama (Jurnal Teknologi dan Mutu Pangan, 2024)
Crude palm oil (CPO) is oil synthesized from the flesh of the palm fruit. CPO has several components that determine its quality, such as moisture content, impurity content, free fatty acid content (FFA), Deterioration of Bleachability Index (DOBI), carotene content, and Iodine Value (IV). Analysis of the physicochemical properties of CPO is needed to determine the quality of the CPO produced, by comparing the test results with the applicable quality standards. This study aims to analyze the quality of CPO produced by PT XYZ and compare it with the SNI 01-2901-2006 quality standard applicable in Indonesia. This research was conducted using the CPO sampling method from PT XYZ. The parameters observed include moisture content, dirt content, ALB, DOBI, and copper and iron metal content. The analysis results show that the moisture content, impurity content, and FFA of PT XYZ CPO samples have met the CPO quality requirements in accordance with SNI provisions. The tested crude palm oil has an average value of 12% moisture content, 0.02% impurity content, ALB 3.33% DOBI 2.38, Cu content 0.31 ppm and Fe content 4.82 ppm. This research makes an important contribution in assessing the quality of crude palm oil (CPO) produced by PT XYZ, ensuring that critical parameters such as moisture content, dirt content, and ALB are in accordance with SNI quality standards, so that the results can be a guideline for the palm oil industry in maintaining the quality of its products.